ChemInform Abstract: Concise Synthesis of Dictyoquinazol A via a Dimerisation—Cyclocondensation Sequence. Issue 40 (September 2016) - Wangsahardja, Jonatan; Marcolin, Gabriella M.; Lizarme, Yuvixza; Morris, Jonathan C.; Hunter, Luke
Abstract: Dictyoquinazol A (I) is obtained by a two‐step total synthesis in 19% overall yield.